Faktor yang Mempengaruhi Perilaku Mahasiswi Kesehatan dalam Akses Informasi Hak Kesehatan Reproduksi pada Perempuan Disabilitas - Santy Irene Putri (Universitas Widya Gama Mahakam Samarinda, 2021)
Background: The role of health students in providing information about reproductive health is very important, especially regarding reproductive health rights for women with disabilities. This is crucial to do because women with disabilities are very vulnerable to violence and discrimination, especially in terms of reproductive health. Objectives: This study aimed to analyze the influence of knowledge and intention toward behavior of female health students in accessing information on reproductive health rights for women with disabilities. Research Methods: This was a quantitative study with a cross-sectional design. This study was conducted at the Midwifery Study Program at Tribhuwana Tunggadewi University Malang in October 2020. The sample size was 50 subjects, selected by simple random sampling technique. The dependent variable is the behavior of health female students in accessing information. The independent variables were knowledge and intention in access to information. Data collection using an online questionnaire. The data analysis technique used multiple linear regression. Results: The behavior of health female students in access to information was influenced by knowledge (b= 0.36, CI 95% = 0.12 to 0.60, p= 0.005), and intention in access to information (b= 0.45, CI 95% = 0.10 to 0.80, p= 0.014). Conclusion: Participants with good knowledge and high intention in access to information affect behavior in accessing information